2018
DOI: 10.1016/j.soard.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral rating system predicts weight loss and quality of life after bariatric surgery

Abstract: A behavioral rating scale (CCBRS) completed before bariatric surgery predicted postoperative weight loss, quality of life, depression, and anxiety. Therefore, this tool may prove useful in patient counseling and expectation management before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
3
7
0
1
Order By: Relevance
“…Generalizability. Overall, characteristics of the sample at baseline were comparable to previously published studies (e.g., Driscoll et al, 2016;Garb et al, 2009;Hilgendorf et al, 2018;Sjöström et al, 2007;Sockalingam et al, 2017). The exception was current and lifetime estimates of psychiatric disorders, which tend to be higher in the bariatric literature than what was found in this study (Kalarchian et al, 2007;Mitchell et al, 2012).…”
Section: Strengths and Limitationssupporting
confidence: 83%
See 1 more Smart Citation
“…Generalizability. Overall, characteristics of the sample at baseline were comparable to previously published studies (e.g., Driscoll et al, 2016;Garb et al, 2009;Hilgendorf et al, 2018;Sjöström et al, 2007;Sockalingam et al, 2017). The exception was current and lifetime estimates of psychiatric disorders, which tend to be higher in the bariatric literature than what was found in this study (Kalarchian et al, 2007;Mitchell et al, 2012).…”
Section: Strengths and Limitationssupporting
confidence: 83%
“…Postsurgery, average anxiety and binge eating scores were within the normative range, whereas depressive symptoms fell within the mild range. Overall, scores on self-report measures were comparable to other studies of bariatric surgery patients (e.g., Hilgendorf et al, 2018;Sockalingam et al, 2017).…”
Section: Aim 2: Predictive Validity Of the Bipasssupporting
confidence: 78%
“…The greater curvature, gastric antrum, pyloric region, and duodenal bulb of the stomach are resected during the SG procedure, which not only decreases the volume of the stomach but reduces the volume of food consumption. SG represents one of the most effective interventions for severe obesity, and its underlying mechanisms for weight loss and metabolic improvement are complex [12].…”
mentioning
confidence: 99%
“…To date there is no clear evidence regarding the impact of pre-operative mental health conditions and of depression specifically, on post-BS weight outcomes. Multiple studies have found preoperative depression to negatively impact weight loss [11][12][13][14], while several others have found no association [5,8,9,[15][16][17][18][19][20][21][22][23]. Some studies have also found a positive link with pre-operative depression resulting in greater weight loss [24][25][26].…”
Section: Discussionmentioning
confidence: 99%